Visual Hallucinations in PD and Lewy Body Dementias: Old and New Hypotheses - M. Onofrj; J. P. Taylor; D. Monaco; R. Franciotti; F. Anzellotti; L. Bonanni; V. Onofrj; A. Thomas (Behavioural Neurology)
Visual Hallucinations (VH) are a common non-motor symptom of Parkinson’s Disease (PD) and the Lewy body dementias (LBD) of Parkinson's disease with dementia (PDD) and Dementia with Lewy Bodies (DLB). The origin of VH in PD and LBD is debated: earlier studies considered a number of different possible mechanisms underlying VH including visual disorders, Rapid Eye Movement (REM) Sleep Intrusions, dysfunctions of top down or bottom up visual pathways, and neurotransmitter imbalance.